Penyuluhan Hukum Status Anak Lahir Diluar Nikah menurut Undang-Undang Nomor 1 Tahun 1974 - Sanawiah Sanawiah; Muhammad Syahrial Fitri; Maimunah Maimunah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
News of the discovery of babies thrown out by biological parents, students giving birth to their children in the toilet due to illicit relationships or adultery, almost every day, both through newspapers and television news, about crimes committed by teenagers in Central Kalimantan, especially the City of Palangka Raya. This is the situation that has led us to hold counseling to schools — community service activities in the form of the counseling legal status of children born out of wedlock according to Law Number 1 of 1974. The methods in this counseling are lecture, discussion, and question and answer methods to provide knowledge and understanding of the status of children born out of wedlock, to people, especially people old, teacher and children of Muhammadiyah II Palangka Raya High School in Kalampangan. Community service activities in the form of counseling legal status of children born outside of marriage according to Law Number 1 of 1974 in Muhammadiyah High School II Kalampangan can make the counseling participants keep themselves and their families from acting in violation of religious norms and legal norms, and can convey to friends the surrounding community about the status of children out of wedlock, according to the Marriage Law Number 1 of 1974 and the opinion of four Islamic Ulemas.